Reliability and validity of a brief questionnaire to assess television viewing and computer use by middle school children. - Schmitz KH; Harnack L; Fulton JE; Jacobs DR Jr.; Gao S; Lytle LA; Van Coevering P (Journal of School Health, 2004)
Sedentary behaviors, like television viewing, are positively associated with overweight among young people. To monitor national health objectives for sedentary behaviors in young adolescents, this project developed and assessed the reliability and validity of a brief questionnaire to measure weekly television viewing, usual television viewing, and computer use by middle school children. Reliability and validity of the Youth Risk Behavior Survey (YRBS) question on weekday television viewing also were examined. A brief, five-item television and computer use questionnaire was completed twice by 245 middle school children with one week apart. To concurrently assess validity, students also completed television and computer use logs for seven days. Among all students, Spearman correlations for test-retest reliability for television viewing and computer use ranged from 0.55 to 0.68. Spearman correlations between the first questionnaire and the seven-day log produced the following results: YRBS question for weekday television viewing (0.46), weekend television viewing (0.37), average television viewing over the week (0.47), and computer use (0.39). Methods comparison analysis showed a mean difference (hours/week) between answers to questionnaire items and the log of -0.04 (1.70 standard deviation [SD]) hours for weekday television, -0.21 (2.54 SD) for weekend television, -0.09 (1.75 SD) for average television over the week, and 0.68 (1.26 SD) for computer use. The YRBS weekday television viewing question, and the newly developed questions to assess weekend television viewing, average television viewing, and computer use, produced adequate reliability and validity for surveillance of middle school students.